Analysis of Non-Technical Losses and its Economic Consequences on Power System - Singh, Tejinder (My University, 2009)
India faces endemic electrical energy and peaking shortages. The Power Sector is plagued with mounting commercial losses due to various inefficiencies, colossal commercial and technical losses and increasing subsidy burden on the states. These shortages have had a very detrimental effect on the overall economic growth of the country. As total distribution system losses equals technical losses plus non-technical losses. The reasons cited for such high losses are; lack of adequate T & D capacity, too many transformation stages, improper load distribution and extensive rural electrification etc. A non-technical loss is defined as any consumed energy or service which is not billed because of measurement equipment failure or ill intentioned and fraudulent manipulation of said equipment. Therefore, detection of non-technical losses includes detection of fraudulent users. Simply Losses could be defined as the difference between the metered units of electricity entering the distribution network and those leaving the network paid for through electricity accounts, whether estimated or metered, in a well defined period of time. When defined by percentage, losses may be referred either to emissions or to withdrawals but the adoption of a common standard is regarded as an important step towards enabling the comparison of losses across network operators. In order to study non technical losses which constitute a portion of the total losses in electrical power systems, the logical first step is to understand the complete picture of power systems losses. Technical losses are regarded as the electrical system losses which are caused by network impedance, current flows and auxiliary supplies. The sources of technical losses may be directly driven by network investment or by network operation. Non-technical losses, sometimes referred to as commercial losses, arise from several areas including theft, un-billed accounts, estimated customer accounts, errors due to the approximation of consumption by un-metered supplies and metering errors. The purpose of this thesis is to perform an introductory investigation of Non Technical Losses with the help of a case study in power systems. These are losses in power systems that cannot be predicted or calculated beforehand because the main reason for non technical loss is Electricity theft. Electricity theft is part of a phenomenon known as “Non- Technical Losses” (NTL) in electrical power systems.
Keywords: Non-Technical Losses; Power System